Flight Vehicle Aerodynamics - Drela (MIT Press, 2014)
Monograph
fulltext
Keywords: Aerospace; Transportation; Signal Processing and Analysis; Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing